2011
DOI: 10.1177/0143831x11419249
|View full text |Cite
|
Sign up to set email alerts
|

The changing role of employment tribunals: The case of the Employment Appeals Tribunal in Ireland

Abstract: Employment tribunals were first established to provide a cheap and accessible service for the quick resolution of legally based employment disputes. With the decline of collective industrial relations and the growth of legislation on individual employment rights, employment tribunals have acquired a new prominence. However, in doing so employment tribunals have also been heavily criticized for becoming too legalistic and formal. This article takes issue with this tendency to criticize the work of employment tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The rights-based judgement approach offered by tribunals is less than effective (Ury et al, 1993). Research has increasingly suggested that whilst tribunals still have a key role to play in dispute resolution, they struggle to deliver informal, speedy and cost-effective dispute resolution (Hann and Teague, 2012; Sander, 1976). This problematization of public bodies as the route to dispute resolution surfaced earliest in the USA, but the debate around delays and costs of tribunals is present throughout much of the developed world, albeit varying in pace and direction from one jurisdiction to another (Roberts and Palmer, 2005).…”
Section: Explaining the Development Of Adrmentioning
confidence: 99%
“…The rights-based judgement approach offered by tribunals is less than effective (Ury et al, 1993). Research has increasingly suggested that whilst tribunals still have a key role to play in dispute resolution, they struggle to deliver informal, speedy and cost-effective dispute resolution (Hann and Teague, 2012; Sander, 1976). This problematization of public bodies as the route to dispute resolution surfaced earliest in the USA, but the debate around delays and costs of tribunals is present throughout much of the developed world, albeit varying in pace and direction from one jurisdiction to another (Roberts and Palmer, 2005).…”
Section: Explaining the Development Of Adrmentioning
confidence: 99%
“…2014). Organizations involved in employment rights cases before either civil courts or bodies like employment tribunals are almost certain to lose on procedural grounds if they do not possess formal disciplinary and grievance procedures (Hann and Teague ). Keeping on the right side of the law has not only prompted change within non‐unionized firms, it has also done so in other organizations such as small firms, which otherwise have a preference for informal conflict management methods (Harris et al .…”
Section: The Changing Political Economy Of Workplace Conflictmentioning
confidence: 99%
“…However, unlike our study, Marsden does not distinguish between different types of employment relations (cooperative versus adversarial) when looking at the relation between legal rights and actual participation patterns. To the contrary, Hann and Teague (2012), analysing the role of employment tribunals, come to the conclusion that the influence of law is steadily growing, and that legalistic and rights-based actions play a key role in the functioning of employment relations systems in Anglo-saxon countries -even in an arena where they should probably not play such a big role. 3 Our distinction is similar to what Rolfsen (2011) calls traditional (employment) relations on the one hand vs. labour-management partnership on the other.…”
mentioning
confidence: 99%